Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/1828051x.2016.1263546
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary α-lipoic acid on carcass characteristics, antioxidant capability and meat quality in Hainan black goats

Abstract: The effects of a-lipoic acid (LA) on the carcase characteristics, antioxidant capability and meat quality of Hainan black goat were investigated in the present study. Thirty goats (10.71 ± 0.42 kg) were randomly assigned with three levels of LA in the concentration diet (0, 300, 600 mg/kg). The goats fed for 70 days. The results showed that goats fed the diet containing 600 mg/kg LA had a significantly (p < .05) higher ADG and better feed conversion rate (FCR) compared with goats offered the basal diet without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Probiotics in a sense are live, naturally occurring microbes (bacteria and yeast) [ 1 ] which when administered in adequate amounts, confers health benefits on the host. Yeast products and their derivatives (i.e., yeast cell wall products) are utilized for a variety of reasons encompassing performance enhancement and overall benefits to animal health and well-being [ 2 ]. The transition period between the late pregnancy and early lactation is under a state of natural immunosuppression, which is due to high concentration of plasma cortisol, decreased dry matter intake (DMI), and decreased production of antioxidant defense near parturition, thus leading to the disruption of normal physiology and contributing to periparturient disorders [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics in a sense are live, naturally occurring microbes (bacteria and yeast) [ 1 ] which when administered in adequate amounts, confers health benefits on the host. Yeast products and their derivatives (i.e., yeast cell wall products) are utilized for a variety of reasons encompassing performance enhancement and overall benefits to animal health and well-being [ 2 ]. The transition period between the late pregnancy and early lactation is under a state of natural immunosuppression, which is due to high concentration of plasma cortisol, decreased dry matter intake (DMI), and decreased production of antioxidant defense near parturition, thus leading to the disruption of normal physiology and contributing to periparturient disorders [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The meat-type goat breed has the excellent characteristics of heat resistance (Wang et al, 2014a), in recent years, with the increase in farm size and the number of goats bred, the low farrowing rate and milkability have exerted increasing influence on the scale of Hainan black goat. There were a few reports on the genetic diversity (Zhou et al, 2012), inflammasome components (Zhang et al, 2017) and nutrition regulation methods (Wang et al, 2014b;Wang et al, 2017;Wang et al, 2015b) of Hainan black goat, however, so far, there still no report on the reproductive law of this specific goat species, the study was the first research on the reproduction characteristics of Hainan black goat, we aimed to improve the fertility of this species through uncovering the internal rule of the changing of serum proteins during the whole reproductive cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Hainan black goats are unique species in China, Hainan province. With the climatic feature of hot and humid, the distinct dry rainy season, the black goats have been cultivated as resistance of crude feed, strong disease resistance, early sexual maturity and tender meat quality through natural selection (Wang et al, 2017). For the numerous excellent trait and considerable economic value, nowdays, industrialized farming of east goats has become a trend, and the chief problem was the relatively low reproduction rate and low milk production efficiency (Adamala, 2018;Al-zaqri et al, 2017;Kannan et al, 2018;Maddi et al, 2018;Troujeni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Alpha-lipoic acid has been used as poultry feed supplement since 2001 [ 125 ]. Another study showed that a-LA supplementation in diets could improve the average daily gain, feed conversion ratio, anti-oxidative capacity and meat quality of Hainan black goats, a breed of goats domesticated for their delicious meat [ 126 ]. Results showed that addition of a-LA to feeds enhanced meat quality by decreasing shear force value and drip loss and increasing meat tenderness [ 126 ].…”
Section: Effectiveness Of Alpha-lipoic Acid In Animalsmentioning
confidence: 99%